A Concept of Household Gas Leak Safety System Using MQ-2 Sensor and Embedded-Based Alarm - Simanjuntak, Christopel; Kumaat, Arief Perdana; Joroh, Adelaida; Mpila, Deby A. (Jurusan Teknik Elektro - Politeknik Negeri Manado, 2026)
Liquefied Petroleum Gas (LPG) leakage in domestic and small-industrial sectors constitutes a major threat that frequently triggers fatal accidents, including severe fires and structural explosions. The primary factor behind these high accident rates is the limitation of human senses in detecting gas accumulation during the early stages of micro-leaks, compounded by the lack of continuous environmental monitoring systems. This study aims to formulate a comprehensive concept for an early detection system design for LPG leakage, integrating the MQ-2 semiconductor gas sensor with an Arduino microcontroller as the primary controller. The core focus of this paper is on modeling the hardware architecture, designing the system programming logic, and conducting a theoretical analysis of the integrated warning alarm scheme.The approach method applied in this conceptual research includes extensive literature reviews, logical flowchart design, electronic circuit schematic modeling, and mathematical simulation of component response times. The proposed system concept is engineered to monitor gas particle concentration fluctuations in the air in real-time. Based on the established theoretical parameters, when the MQ-2 sensor detects LPG particles exceeding the predefined safe threshold (set above 400 ppm), the Arduino microcontroller will immediately process the analog signal into a digital command to execute emergency protocols. This action triggers a high-frequency audible alarm via a buzzer and a visual indicator through a red LED light to provide instant warnings to building occupants.The conceptual design results demonstrate that the integration between Arduino and the MQ-2 sensor yields a security system scheme that is not only highly responsive and rapid in calculation but also economical and easy to mass-produce. This paper contributes significant scientific value by delivering a solid, valid, and applicable conceptual blueprint, which can serve as a primary reference for the physical development and manufacturing of smart gas leak detection devices in the future to enhance residential safety standards.